2017
DOI: 10.1016/j.ccr.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Design principles in frustrated Lewis pair catalysis for the functionalization of carbon dioxide and heterocycles

Abstract: This is the peer reviewed version of the following article: [Design Principles in Frustrated Lewis KeywordsFrustrated Lewis pairs, Ambiphilic molecules, Boron, Aluminum, Carbon dioxide, Methanol, C-H activation. Highlights 1.Phosphine-aluminum frustrated Lewis pairs (FLPs) can activate CO2 but show significant stability issues. 2.The Lewis acidity and basicity need to be fine-tuned to the desired reactivity for efficient FLP catalysis.3. FLP catalysts need to generate strong hydrides to reduce catalytically ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 104 publications
(78 reference statements)
1
40
0
Order By: Relevance
“…Since the first example of CO2 activation by FLPs in 2009, 140 its capture and further utilisation has been an attractive target for chemists. 141 In the case of CO2 activation, the basic phosphine attacks the electrophilic carbon atom, whilst one of the electron rich oxygen atoms donates into the empty p-orbital of the borane (Scheme 21).…”
Section: Co2 Activation By Flpsmentioning
confidence: 99%
“…Since the first example of CO2 activation by FLPs in 2009, 140 its capture and further utilisation has been an attractive target for chemists. 141 In the case of CO2 activation, the basic phosphine attacks the electrophilic carbon atom, whilst one of the electron rich oxygen atoms donates into the empty p-orbital of the borane (Scheme 21).…”
Section: Co2 Activation By Flpsmentioning
confidence: 99%
“…Based on the precedents outlined in the Introduction, we envisaged that the activation of CO 2 would be critical to mitigate the selectivity of the carboxylation reaction of al-Scheme 1 (A) -Keto acid formation reactions of aldehyde under CO 2 atmosphere, and attempts at (B) CO 2 reduction with aldehydes, (C) carboxylation, and (D) oxidation with water and air. [11][12][13][14] Particularly, nucleophilic catalysts (i.e., NHCs, amidine, diamines, guanidines, and DMAP derivatives) have been employed in CO 2 activation by forming CO 2 -nucleophile adducts. 15,16 For example, a single-crystal structure analysis of TBD-CO 2 (TBD: 1,5,7-triazabicyclodec-5-ene) complex showed that intramolecular hydrogen-bonding may contribute to the stabilization of the complex.…”
Section: Co -Activation: Nhc Cyanide Lewis Acid and Watermentioning
confidence: 99%
“…Increasingly stringent environmental standards are prompting us to look for clean and efficient methods for the synthesis of organic compounds. In recent years, much attention has been focused on reactions employing simple, nonmetallic P,Bbased [1][2][3][4][5][6] systems that can activate waste gases such as CO, 7,8 CO 2 , [9][10][11][12][13] NO x , 10,14 SO 2 , 14,15 or even H 2 . 5,9,[16][17][18][19] These metal-free reactions not only involve easily accessible and inexpensive gaseous reagents as the feedstock but also enable the straightforward and efficient synthesis of organic compounds through the functionalization of small inorganic molecules.…”
Section: Introductionmentioning
confidence: 99%